2004
DOI: 10.1002/ijc.20722
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical measurement of brain tumor cohesion

Abstract: An advantage of using 3D multicellular spheres to study tumor biology is that they better approximate the interactions encountered by cells in vivo. Our previous studies have shown that the process of spheroid formation is governed by the same thermodynamic principles driving the formation of liquid droplets. This liquid-like behavior enables us to measure a key property influencing tumor behavior, namely, intercellular cohesion. We have developed a method, tissue surface tensiometry (TST), to measure the cohe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
51
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 40 publications
8
51
0
1
Order By: Relevance
“…Using this approach, Iordan et al [20] were able to determine typical intrinsic properties for concentrated suspensions of Chinese Hamster Ovary cells (CHO). Other works deal with different types of cell suspensions [10,12,11,13,42], and similar behaviors are observed. Their interpretation of the experimental data is usually given in terms of a macroscopic mechanism, i.e.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Using this approach, Iordan et al [20] were able to determine typical intrinsic properties for concentrated suspensions of Chinese Hamster Ovary cells (CHO). Other works deal with different types of cell suspensions [10,12,11,13,42], and similar behaviors are observed. Their interpretation of the experimental data is usually given in terms of a macroscopic mechanism, i.e.…”
Section: Introductionsupporting
confidence: 58%
“…Cell aggregates or multicellular systems appear in embryo development [29,28,26,39,24] or in blood flow, but they are also involved in other processes such as hydra aggregates motion, dictyostelium slugs crawling [34,33] and they are of considerable interest in tumour growth [1,2,14,15,42]. Their mechanical behavior is often assimilated to soft biological tissues, usually corresponding to viscoelastic materials or to non-Newtonian fluids [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, from the experimental point of view it is very difficult to perform mechanical tests on living matter, and in particular on ensembles of cells. In this respect Winters et al [WSF05] performed a wonderful and very promising experiment consisting in a uniaxial compression test. More precisely, multicellular spheroids with radii in the range 0.15-0.7 mm were positioned between two plates immersed in a physiological liquid.…”
Section: Stress Tensorsmentioning
confidence: 99%
“…The same equation used to measure the surface tension of a liquid droplet is used to measure intercellular binding energy of 3D tissue-like spherical aggregates. Previous studies have shown that TST measurements (1) predict how two groups of embryonic cells will interact with one another (Foty et al, 1994(Foty et al, , 1996Davis et al, 1997); (2) correlate inversely with the degree to which aggregates spread upon biomaterials (Ryan et al, 2001); (3) correlate inversely with invasive potential of lung tumors (Foty and Steinberg, 1997), fibrosarcomas , and brain tumors (Winters et al, 2005); and (4) can be altered not only through direct manipulation of cadherin-based intercellular cohesion (Foty et al, 1999;Duguay et al, 2003), but also by manipulation of extracellular matrix molecules such as fibronectin (Robinson et al, 2003(Robinson et al, , 2004. For comprehensive reviews, see Steinberg (2004, 2005).…”
Section: Introductionmentioning
confidence: 99%